Fruit rind constituents in nutmeg (Myristica fragrans) morphotypes - Mini Raj, N.; Vikram, H.C.; Philip, Manu; Deepa, E.T. (Journal of Plantation Crops, 2017)
Rind or pericarp is the outermost part of nutmeg fruit which is thick and fleshy. Fresh rind, contributing 80 to 85 per cent of total fruit weight, has an astringent taste with aromatic flavour. Due to these qualities, the use of rind for food purpose is restricted. At the same time its therapeutic property, especially its anti-oxidant, anti-microbial and anti-diarrhoeal effects, have generated interest in nutmeg rind. Major interest of the processors is the biochemical constitution of the rind. In the present study, 17 distinctly featured nutmeg accessions selected from core collections in central Kerala were employed for biochemical analysis of rind. A total of 10 constituents of ripe rind were estimated using standard analytical techniques. Data were statistically analysed and sub groups formed using DMRT. The range of variation was 87.1 to 89.1 (mg 100 g-1) for ascorbic acid, 0.2 to 1.08 per cent for pectin content (calcium pectate), 0.21to 1.85 (g 100 g-1) for protein, 0.3 to 1.23 (g 100 g-1) for starch, 27.8 to 57.6 (mg 100 g-1) for total phenol, 143.3 to 750.0 (mg 100 g-1) for tannin, 2.01 to 2.57 per cent for total minerals and 2.06 to 3.65 per cent for crude fibre. Since varied overlapping sub-groups were obtained constituents wise, the method to make decisions jointly on a number of dependant characters was co-opted. The final score is an indicator of the relative superiority of the accessions in terms of the biochemical constituents of rind. The accessions were categorized for various end uses based on the score obtained for each constituent. The variation in biochemical composition may be due to inherent genetic character of the tree as also the geographic location and management practices followed. Based on the composition, the nutmeg rind, which at present is discarded as a farm waste, could be utilized for value addition in the food, nutraceutical and pharmaceutical sectors.